Comparing the Accuracy of Conventional with Direct Digital Radiographic Method in Diagnosing the Periapical Lesions - Lohe, Vidya K.; Gupta, Supriya V.; Kadu, Ravindra P.; Sune, Ravikant V.; Mohod, Swapnil C.; Meshram, Mrunal G. (Journal of Datta Meghe Institute of Medical Sciences University, 2024)
Background: Traditionally, the conventional radiograph forms the primary imaging modality in diagnosing, treating, and carrying out the follow-up of periapical lesions. Early lesions are hard to identify precisely due to the diffused and infiltrative characteristics of the inflammatory course in bone. There is much controversy concerning the precision of imaging technique in identifying radicular lesions. Materials and Methods: One hundred and fifty dentate patients with the age range of 16 years and above were recruited. After clinical examination of the subjects, conventional films and digital images were obtained separately on the same case by employing the bisecting angle technique for acquiring direct digital and conventional radiographic images. The digital images viewed by the observers and results were tabulated for statistical analysis. Results: Radiographic diagnostic accuracy in diagnosing the periapical processes was more by digital radiography than the conventional one. Conclusion: The results demonstrate that the conventional radiograph being the gold standard has more diagnostic accuracy in measuring periapical lesions. Digital radiographs can be used as an alternative with the advantages being that there is no use of processing solution and the ability to enhance image, data storage, and diagnostic value also can be changed by the operator.